Tiffin habits of school children - Mital, Premlata; Hooja, Ribhu; Lauria, Nupur (International Journal Of Community Medicine And Public Health, 2022)
Background: The “mid-day meal scheme” is the popular name for the school meal program of India, through which meal is provided to school children studying in the government and government aided schools. In non-government schools, children carry tiffin’s from home. Often, due to lack of time and/or knowledge of the parents and students, the contents of the food are not as per a balanced diet. The objective of the study was to analyse and compare the tiffin habits of primary and senior school children. Methods: This was a clinic-based study. Parents of 300 school going children were asked about tiffin habits of their children in a predesigned questionnaire. Data was analysed and conclusions drawn. Results: Most children carried tiffin to school on the majority of days. There was no statistical difference between primary or older children in their tiffin contents. Very few primary school children had a say in the content of tiffin. The senior students spent money in canteen on more days per week, whereas most primary class students spent only once a week or for treats. Conclusions: It is crucial for schools to establish food committees in school that suggests and monitors tiffin policies and meal plans based on nutrition.